Navigation control and stability investigation of a mobile robot based on a hexacopter equipped with an integrated manipulator. (24th November 2017) - Božek, Pavol; Al Akkad M, Aiman; Blištan, Peter; Ibrahim N, Ibrahim
In this article, the dynamics model of a hexacopter equipped with a robotic arm has been formulated using Newton–Euler's method and its stability was investigated. For disturbances emulation, a simplified pendulum method was used. This hexacopter configuration was not covered in scientific papers before. The resulting model is a nonlinear, coupled, and underactuated dynamics model, which includes aerodynamic effects and disturbances because of equipping the hexacopter with a robotic arm. The purpose of the presented article is to offer a comprehensive study of determining the inertia moments of the hexacopter using a simplified pendulum method, taking into consideration the effect of mass distribution and center of gravity changes, which are a result of the continuous movement of the manipulator during the hexacopter motion in the air. The experimental tests were made using SolidWorks application and were evaluated using LabVIEW in order to get a complete view of the disturbances, which were inserted into the dynamics model. The overall aircraft model was driven by four classical proportion, integral, and derivative controllers for the vehicle's attitude and altitude of a desired trajectory in the space. These controllers were used to get a good understanding of how to evaluate and validate the model to make it an anti-disturbance model, in addition to their ease of design and fast response, but they require development in order to get optimal results. In future, a precise trajectory will be defined, and the controllers will be developed in order to get robust stability using nonlinear techniques and artificial intelligence.